THE STATE, SHIA, AND EXCLUSIONARY POLICIES IN MAKASSAR – INDONESIA (JOURNAL OF INDONESIAN ISLAM, 2023)
This study examines the Shia minority in Makassar, South Sulawesi, who was excluded by anti-Shia groups, and received support from the local government. The exclusion of Shia in Makassar is contrary to the constitution in Indonesia which guarantees freedom of religion for all religious people, including the Shia group. The purpose of this study is to explain that the act of exclusion against the Shia group in the public sphere is against the Constitution. From this study, there is an urgency to build religious inclusivity and equality in democratic public policies. This study uses a qualitative approach with primary data collection methods conducting in-depth interviews with several competent informants in Makassar.